CAUSATIVE CONSTRUCTION IN ACEHNESE LANGUAGE: X-BAR THEORY ANALYSIS - Juliana; Mulyadi (Universitas Duta Bangsa Surakarta, 2025)
Causative Constructions are central to understanding how languages encode cause-and-effect relationships. In Austronesian languages, they exhibit diverse strategies ranging from affixation to periphrastic structures. This research investigates causative constructions in Acehnese language with the aim of identifying their main types and analysing their structures through X-Bar Theory. Data were collected from native Acehnese speakers via field observations, semi-structured interviews, and supported with written texts, and were analysed using a qualitative descriptive approach. The findings reveal two structural patterns: mono-clause (single-clause) and bi-clause (two-clause) constructions. Within these, three causative types emerge: (1) morphological causatives, formed with prefixes such as peu- and seu- that increase a verb’s argument structure (valency); (2) paraphrastic causatives, employing auxiliary verbs such as geu-yue and peu-gèt in bi-clause constructions; and (3) semantic causatives, where verbs like geu-plén inherently encode causative meaning without structural modification. Morphological and semantic causatives are generally mono-clause, while paraphrastic causatives are typically bi-clause. Applying X-Bar Theory enables a formal representation of how the causer (initiator), cause (event), and causee (affected participant) are hierarchically organized in Acehnese syntax, revealing systematic patterns of valency shift and clause complexity. Unlike most previous studies, which have largely offered descriptive accounts, this research demonstrates how X-Bar Theory—rarely applied to Acehnese language—can capture the interaction between morphology, semantics, and syntax in a formal model. In short, this research not only enriches the description of Acehnese language causatives but also fills a theoretical gap by contributing a formal syntactic representation of Acehnese language causatives through X-bar theory, an approach rarely explored in previous researches and contributed to broader discussions of syntactic theory in Austronesian languages.